Analisis Kesalahan Siswa Berdasarkan Newman Ditinjau dari Tingkat Kecemasan Matematis - Rizki Nurhana Friantini; Rahmat Winata (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2020)
This study aims to analyze the types of student errors based on Newman in terms of the level of mathematical anxiety. This type of research is qualitative research. Research subjects were 9 students of class XIII Maniamas Middle School consisting of 3 students for each level of mathematical anxiety. Subject selection with purposive sampling. Data collection using test and interview methods. The validity of the data uses method triangulation. The results of this study are students from low mathematical anxiety levels producing errors in the form of process errors and coding errors . Students from the level of mathematical anxiety are producing errors in the form of transformation errors, calculation errors, and coding errors. Students from high levels of mathematical anxiety produce errors in the form of comprehension errors, transformation errors, process skills errors, and encoding errors.